Religious Values In The Verses Of The Traditional Ceremony Of The People Of Aceh Besar - Yulsafli Yulsafli; Sariakin Sariakin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research topic discusses the religious values ​​contained in a poem by analyzing the poems of the traditional ceremony of turun tanah (land descent) of the Aceh Besar community. The research was conducted using a descriptive qualitative approach and content analysis of the poems. Data were collected through observation, interviews, and audio-video recordings, then analyzed qualitatively. The results of the study indicate that poems such as Marhaban, Tala'al Badru 'Alayna, Mahalluqiyamin, Ya Nabi Salam 'Alaika, Keu Aneuk Manyak, and Peutron Aneuk contain religious values ​​in the form of traditional rituals that serve as a medium for character education. The value of worship is evident in the poems of marhaban, shalawat, and prayers offered as a form of obedience to Allah and respect for the Prophet Muhammad. The value of ruhul jihad reflects the spirit of struggle inherited through the poem Tala'al Badru 'Alayna, which depicts the Prophet's journey of hijrah as a symbol of the struggle to establish Islam. The value of exemplary behavior is strengthened by depicting the Prophet Muhammad as a role model to be emulated in everyday life. The value of trust is evident in prayers that children grow into obedient individuals who are responsible to God, their parents, and society. Meanwhile, the value of sincerity is evident in the prayers and hopes offered by parents selflessly, solely for God's pleasure.